2015
DOI: 10.11591/edulearn.v9i3.2301
|View full text |Cite
|
Sign up to set email alerts
|

The Application of School Watching Method to Increase the Earthquake Disaster Knowledge of Primary School Students

Abstract: The study entitled "The Application of School Watching to Increase the Earthquake Disaster Knowledge of Primary School Students, MIN Blang Mancung, Aceh" was aimed to describe the students' knowledge of the different dangerous objects in the face of an earthquake. The approach used in this study was qualitative and quantitative. The type of study was descriptive. Subjects used were as many as 30 students MIN Blang Mancung, Aceh. The method used was an experimental, which was divided into two classes, namely th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
0
6
0
Order By: Relevance
“…The study concluded that there is an influence between Kindergarten Watching and stimulation of visual spatial and kinaesthetic intelligence in children. Sari & Khatimah [12] also performed another adoption. This study concluded that the preparedness attitude of students at MIN Blang Mancung increased with the application of the School Watching method.…”
Section: Resultsmentioning
confidence: 99%
“…The study concluded that there is an influence between Kindergarten Watching and stimulation of visual spatial and kinaesthetic intelligence in children. Sari & Khatimah [12] also performed another adoption. This study concluded that the preparedness attitude of students at MIN Blang Mancung increased with the application of the School Watching method.…”
Section: Resultsmentioning
confidence: 99%
“…The school-watching method is a method that can help the students increase disaster preparedness by doing activities to identify hazardous objects when an earthquake happens [25]. The school-watching method developed into several approaches, such as campus-watching and town-watching [26].…”
Section: Methodsmentioning
confidence: 99%
“…The linkage of knowledge of disaster mitigation with children at the elementary school level is described (Sari et al, 2014) to build a culture of security and resilience in the face of disasters. Students are able to act quickly, precisely and accurately when facing disasters (Desfandi, 2014), from the knowledge they have can help people to save themselves and their groups in the future (Marskole et al, 2018).…”
Section: Introductionmentioning
confidence: 99%